Pengetahuan Ibu Dan Kepatuhan Ibu Tentang Penggunaan Kontrasepsi Di Masa Pandemi - Desi Ekawati; Retno Heru Setyorini (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2023)
Background: The world's population continues to grow, Indonesia is also predicted in2025-2035 to be the fourth most populous country in the world. For this reason, it isnecessary to control the rate of population growth through the family planning programusing contraception. During the pandemic, it had several impacts, especially for theFamily Planning (KB) program, namely: a decrease in family planning participants.Ultimately it will affect family planning services and membership. Family planningparticipants during a pandemic were afraid to make repeat visits because of their limitedknowledge of family planning during a pandemic.Research objectives for the relationship between mother's knowledge aboutcontraception and adherence to contraceptive use during the pandemic.Subjects and Methods This research uses non-experimental research with anobservational research design that aims to analyze a relationship between variables. Thistype of research uses cross sectional. The sampling technique in this study was simplerandom sampling. The subjects in this study were mothers who used contraception inDelanggu Village as many as 55 acceptors.Results: Based on the research, it can be found that out of 55 respondents, the majorityof respondents have knowledge about contraceptive use in the good category, namely26 respondents (47.48%). 30 respondents (54.5%) were obedient in using contraception,it was found that there was a significant relationship between mothers' knowledge aboutcontraceptive use and adherence to contraceptive use during a pandemic with a p value= <0.001.Conclusion: Mother's knowledge of contraceptive use during a pandemic is good,adherence to contraceptive repeat visits during a pandemic is good and there is asignificant relationship between maternal knowledge and maternal compliance incontraceptive services (p <0.001).Keywords: contraception, pandemic, compliance, knowledge, Covid19